Probing basis set requirements for calculating core ionization and core excitation spectra using correlated wave function methods - Ambroise, Maximilien; Dreuw, Andreas; Jensen, Frank (Journal of chemical theory and computation, 2021)
We investigate the basis set requirements for the accurate calculation of core excitations and core ionizations using correlated wave functions of coupled cluster type and linear response methods for describing the excitation. When a core excitation is described as an energy difference calculated using density functional theory, the basis set can be tailored to provide a balanced description of the reference- and excited-hole states. When the core excitation process is described by coupled cluster linear response methods, however, the basis set requirements are somewhat different. A systematic study of the sensitivity of the result to the basis set parameters suggests that a relatively large set of s- and p-type basis functions in combination with a careful selection of valence and core polarization functions is required. Based on these results, we propose a hierarchical sequence of basis sets, denoted ccX-nZ (n = D, T, Q, 5) for the atoms B-Ne, which are suitable for the calculation of core excitations by the correlated wave function linear response and equation-of-motion methods. The ccX-nZ series provides lower basis set errors for a given cardinal number or number of basis functions than other existing basis sets. For large systems, the ccX-nZ basis sets can be combined with the standard basis sets by placing the ccX-nZ only on the atoms where core excitations are of interest, but the accuracy of such mixed basis sets appears to be system-dependent.